Kazakhstan Studies: global research discourse and local narratives - Nazira Abdinassir; Svetlana Kovalskaya (Turkic Studies Journal)
This article explores the contributions of foreign scholars to the study of Kazakhstan, emphasizing their role in deepening understanding of its historical and contemporary context within a global framework. It examines Kazakhstan’s historiography from the perspective of Western academic discourse. By employing diverse theoretical and methodological approaches, these scholars enhance research on Kazakhstan’s historical and sociocultural dynamics, focusing on its ethnic diversity, cultural heritage, and geopolitical significance. Using qualitative research methods, including in-depth interviews with international historians specializing in Kazakhstan, this study aims to identify key themes of their research and explore future directions. Between May 2024 and February 2025 six interviews were conducted, one of which involved written responses to a questionnaire. The interviewees were distinguished scholars from the United States, Canada, Italy, and Japan, all recognized experts in the region’s history. Free from the ideological influences of Soviet historiography, they possess advanced knowledge of Central Asian languages, have conducted extensive research in Kazakhstan’s archives and libraries, and maintain professional connections with Kazakhstani scholars. The interviews, conducted in English, followed a structured questionnaire. The majority of these interviews were conducted at prominent international conferences organized by the Central Eurasian Studies Society (CESS) and the European Society for Central Asian Studies (ESCAS). However, conducting these interviews posed challenges. The intensive conference schedules made arranging in-person meetings with scholars and effectively coordinating discussions difficult. Additionally, some interviewees were slow to respond to email inquiries, limiting the completeness of the dataset. This study demonstrates how the research conducted by these scholars not only advances academic study of Kazakhstan but also integrates local narratives into global scholarly discussions. Their contributions help train a new generation of researchers in Kazakhstani history and culture. Organizations such as CESS and ESCAS play a crucial role in fostering academic exchange and promoting scholarship in Kazakhstan. The insights from these interviews reflect a growing international interest in Kazakhstan’s history and culture, underscoring the valuable contributions of foreign scholars in enriching academic discourse and global perspectives on the region.